Pengaruh Kompetensi Lulusan Berbasis Entrepreneurship Terhadap Kepuasan Pengguna Dan Daya Saing Alumni Sekolah Tinggi Ilmu Ekonomi Bima - Juwani; Hanifah Muthiah (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
. The aim of this research is to determine the direct relationship between entrepreneur-based competencies on user satisfaction and alumni competitiveness. This research uses a quantitative approach method by distributing questionnaires. The population in this research is all organizations/agencies using STIE Bima alumni whose numbers are unknown. The sampling technique used was purposive sampling, namely 50 organizations/agencies that employ alumni, both private and government. The data analysis tool uses Smart PLS. The results of this research provide information that Interpreneur-Based Graduate Competencies have a direct influence on User Satisfaction and Competitiveness of Bima College of Economics Alumni